LINGKUNGAN PENGENDAPAN SATUAN BATULEMPUNG SISIPAN BATUPASIR PADA FORMASI KEREK DAERAH JUWANGI DAN SEKITARNYA, BERDASARKAN KARAKTERISTIK LITOLOGI, ANALISIS STRUKTUR SEDIMEN, DAN KANDUNGAN FOSIL BENTONIK - Morina, Hana; Syafri, Ildrem; Jurnaliah, Lia (Bulletin of Scientific Contribution, 2014)
The research area is located in the Juwangi, Grobogan District, Central Java Province. Geographically located between 110o 44’ 19,536” BT – 110o 49’ 19,5384” BT dan 7o 13’ 53,2704” LS – 7o 8’ 53,2716” LS. Research using the method geological surface mapping. Determination of depositional environment unit based on the characteristic of lithology, sedimentary structures, and benthic foraminiferal. Based on the characteristic of lithology, this unit composed of mudstone and sandstone. Mudstone has a consideralable thickness, as sandstones insert. Sedimentary structures that are found in the form of parallel lamination and cross lamination shows that its transport medium is water. Benthic foraminiferal analysis result indicate that the bathymetry zone is outer neritic. So it can be estimated that the depositional environment of this unit are in the shallow marine.